(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article will cover the history of the emergence of ensuring the security of participants in criminal proceedings, how participants in criminal proceedings, in particular witnesses and victims, were protected in Ancient Greece, as well as in Medieval Europe, as well as in Islamic law.